2003
DOI: 10.1097/01.ju.0000096221.67967.ae
|View full text |Cite
|
Sign up to set email alerts
|

Salvage of Sildenafil Failures Referred From Primary Care Physicians

Abstract: Approximately 40% of patients with sildenafil failures referred from PCPs can be converted to responders through reeducation. Incorrect drug administration was the most common reason for correctable failure. Reeducation can be done in an efficient manner. New package materials may improve sildenafil outcomes and compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 8 publications
2
52
0
Order By: Relevance
“…These results confirmed by Atiemo et al [11]. Incorrect administration accounted for 81% of sildenafil failures referred by primary care physicians.…”
Section: Identifying Truly Treatment Failuressupporting
confidence: 81%
“…These results confirmed by Atiemo et al [11]. Incorrect administration accounted for 81% of sildenafil failures referred by primary care physicians.…”
Section: Identifying Truly Treatment Failuressupporting
confidence: 81%
“…19 When these guidelines were followed, 74% of 111 consecutive men with ED who visited a urology clinic and were enrolled in a goal-oriented disease management program reported successful intercourse with sildenafil 50 or 100 mg, and 54% of 76 previous sildenafil nonresponders identified by retrospective chart review became responders. 76 The impact of reeducation and of titration to the maximum tolerated sildenafil dose is also supported by the results of Atiemo et al, 77 who reported a 42% (98/236) success rate in former sildenafil nonresponders, and by Jiann et al, 78 who reported a 59% (24/41) success rate in former sildenafil nonresponders. In these studies, incorrect administration (after heavy meals, lack of sexual stimulation, improper timing, too few attempts, and maximal dose o100 mg) was the most frequent cause for nonresponse to sildenafil.…”
Section: Optimizing Sildenafil Treatment To Maximize Effectivenesssupporting
confidence: 72%
“…20 In all, 100 mg Sildenafil leads to an increase of adverse events such as blurred vision in 11.1%, compared with 2.2% for the dose of 50 mg. 21 Moreover, 40% of sildenafil nonresponders responded to the same dose after the re-education by ED specialists, including the timing of taking the drug or prevention of interaction with food. 22 Thus, 50 mg sildenafil administration with thorough education before prescription remains the mainstay for most Asian men to avoid undesirable complications. Although the definitive reason why Japanese men were satisfied with a lower dose is still unclear, the dose regulation of this country and the detailed information given about the administration of this drug might have affected the efficacy.…”
Section: Discussionmentioning
confidence: 99%